Hubungan Kontrol Diri Guru dengan Intensi Melakukan Kekerasan Terhadap Siswa - Djuwariyah Djuwariyah (Islamic University of Indonesia, 2011)
Violence in school that is performed by teachers occurred because of one of these factors: lack of teaching skills, lack of morality, lack of responsibility and lack of self-control. Teachers with such minor characters are not able to teach properly and are not able to make a good emotional interactions with students. Among those factors, self-control takes into account in supporting teachers to avoid violence towards students. Therefore, the current study aims at researching correlation between teachers self-control with intention to do violence towards students. Using statistical analysis, this research found that there is significant correlation between teachers’ self-control with intention to do violence towards students. It is shown through correlation co-efficient r = -0.684 with p = 0.000 (p